Intelligent monitoring system for fully operational engines - Castillo-Picado, Gerald Alexander (2023)
The proposal is made using Arduino and the use of different sensors, a system can be created that can monitor other risk conditions in three-phase induction motors, such as power supply (current and voltage), vibrations, and motor temperature or environment, for which vibration, temperature and sound sensors are used, this with the intensity of verifying the conditions of the motor through monitoring. This can prevent damage and production losses with early detection of these factors, by notifying managers if the integrity of the engine is at risk and being able to perform preventive maintenance on the system, which is low cost and does not take so long. the production process as would performing corrective maintenance, in the case of damage to the engine or related accessories such as ventilation systems, pumps, and others.